TikTok Content Strategies in Shaping Tourism Interest in Hidden Gem Destinations: The Case of Curug Walet - Utami, Tiara Septia (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2026)
The rapid growth of TikTok has created new opportunities for promoting tourist destinations, including hidden gem locations such as Curug Walet in Bogor. This study aims to analyze how TikTok content strategies contribute to the process of forming travel interest through a combination of platform-specific technical elements and psychological approaches to audiences. Employing a qualitative case study approach, the research draws on in-depth interviews with a content creator, an open-trip service provider, and active TikTok users, complemented by content analysis of relevant videos. The analysis is grounded in Uses and Gratifications Theory, which explains how audiences’ needs for entertainment, information, and emotional experiences are fulfilled through TikTok content. The findings indicate that algorithm optimization, creative feature utilization, and emotional storytelling, particularly through the use of Fear of Missing Out (FoMO), play an important role in shaping audience perceptions and attraction toward the destination. This study highlights that TikTok content strategies function not merely as promotional tools but as a form of experiential communication that shapes audience interest in alternative tourist destinations.